A Review of Renewable Energy Policy and Implementation in Nigeria and Ghana - Dasori Azundow Edmund; Wisdom Elikplim Korkortsi; Ramatu Al-hassan; Collins Dormena; Gloria Opoku Darkoh (Journal of Power, Energy, and Control, 2026)
The global energy transition, driven by the imperatives of climate change mitigation and the pursuit of Sustainable Development Goal 7 (SDG 7), is particularly significant for developing nations in West Africa. This review article synthesizes and critically analyzes the literature on renewable energy policy adoption and implementation in Nigeria and Ghana, two nations with abundant solar, wind, and hydropower resources. The analysis reveals a central thesis: while both countries are committed to a sustainable energy transition, their progress is dictated by divergent institutional, financial, and technical factors. Ghana's more cohesive policy framework and proactive grid upgrades have enabled a higher renewable energy share and more effective project deployment, but it is still constrained by financial and enforcement gaps. In contrast, Nigeria's vast renewable energy potential is significantly underutilized due to a fragmented regulatory framework, underinvestment, and systemic infrastructure deficiencies. This review identifies key research and policy gaps, including the absence of detailed long-term socio-economic modeling and in-depth analysis of tailored financial mechanisms.